Optimal anesthetic conduct regarding immediate and short‐term outcomes after liver transplantation – Systematic review of the literature and expert panel recommendations. Issue 10 (28th February 2022) - Chadha, Ryan; Patel, Dhupal; Bhangui, Pooja; Blasi, Annabel; Xia, Victor; Parotto, Matteo; Wray, Christopher; Findlay, James; Spiro, Michael; Raptis, Dimitri Aristotle; ,
Abstract: Background: In the era of enhanced recovery after surgery, there is significant discussion regarding the impact of intraoperative anesthetic management on short‐term outcomes following liver transplantation (LT), with no clear consensus in the literature. Objectives: To identify whether or not intraoperative anesthetic management affects short‐term outcomes after liver transplantation. Data Sources: Ovid MEDLINE, Embase, Scopus, Google Scholar, and Cochrane Central. Methods: A systematic review following PRISMA guidelines was undertaken. The systematic review was registered on PROSPERO (CRD42021239758). An international expert panel made recommendations for clinical practice using the GRADE approach. Results: After screening, 14 studies were eligible for inclusion in this systematic review. Six were prospective randomized clinical trials, three were prospective nonrandomized clinical trials, and five were retrospective studies. These manuscripts were reviewed to look at five questions regarding anesthetic care and its impact on short term outcomes following liver transplant. After review of the literature, the quality of evidence according to the following outcomes was as follows: intraoperative and postoperative morbidity and mortality (low), early allograft dysfunction (low), and hospital and ICU length of stay (moderate). Conclusions: For optimal short term outcomes after liver transplantation, the panel recommends the use of volatile anesthetics in preference to total intravenous anesthesia (TIVA) (Level of Evidence: Very low; Strength of Recommendation: Weak) and minimum alveolar concentration (MAC) versus bispectral index (BIS) for depth of anesthesia monitoring (Level of Evidence: Very low; Strength of Recommendation: Weak). Regarding ventilation and oxygenation, the panel recommends a restrictive oxygenation strategy targeting a PaO2 of 70–120 mmHg (10–14 kPa), a tidal volume of 6–8 ml/kg ideal body weight (IBW), administration of positive end expiratory pressure (PEEP) tailored to patient intraoperative physiology, and recruitment maneuvers. (Level of evidence: Very low; Strength of Recommendation: Strong). Finally, the panel recommends the routine use of antiemetic prophylaxis. (Level of evidence: low; Strength of Recommendation: Strong).